Uplink capacity analysis of two-hop-relay CDMA cellular systems - LU Wei-feng1; WU Meng2 (Tongxin xuebao)
Based on the two-hop-relay CDMA cellular systems,two kinds of out-of-band relaying methods were pro-posed to improve the conventional CDMA cellular systems.Then by analyzing the interference power of the non-relaying CDMA cellular systems,the overall interference power to own and neighbor cell could be obtained with using these two relaying methods.Finally,based on a symmetrical cell model,the uplink capacity of two-hop-relay CDMA cellular sys-tems was analyzed by mathematical calculating,and the impact of these two relaying methods on system’s performance was discussed.